Regulatory Evolution and Challenges in Aceh’s Sharia Financial System: A Study of Qanun Reforms - Ihwanudin, Nandang; Siregar, Muhammad Rafi; Rifai, Ahmad; Manarul, Achmad (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2025)
As a province operating under Sharia law, Aceh has implemented a Sharia economic system that covers all sectors, including financial institutions. The basic regulation for this system, Qanun Aceh No. 11 of 2008 on Sharia Financial Institutions, establishes the initial framework. However, broader development requires regulatory improvements. This study examines the transformation of the Qanun and its implications for the Islamic economic system in Aceh. Using a normative-empirical legal approach, this study analyses Qanun and field data from Banda Aceh and Lhokseumawe. Informants from the regulatory, banking and community sectors were interviewed. Triangulation and thematic analysis ensured valid findings on the implementation of Islamic economic norms, balancing legal examination with empirical observations of practical challenges and social acceptance. The findings show that although the regulatory framework for Islamic economics in Aceh has developed well, the socio-economic promise of justice and inclusion that it holds is still hampered by implementation gaps, structural barriers, and limited public consensus. The future of Aceh's Islamic economy does not depend on additional legislation, but rather on focused efforts in education, capacity building, and the provision of quality services to build public trust and ensure equitable benefits for all communities. The study highlights legal pluralism studies in decentralized governance and can provide framework for analysing sharia-based economic development models.